2021
DOI: 10.1097/ccm.0000000000004941
|View full text |Cite
|
Sign up to set email alerts
|

Use of Corticosteroids in Cardiac Arrest—A Systematic Review and Meta-Analysis

Abstract: OBJECTIVES: The objective of this systematic review was to evaluate the impact of intraarrest corticosteroids on neurologic outcomes and mortality in patients with cardiac arrest. DATA SOURCES: We conducted a systematic search using the Cochrane Central Register of Controlled Trials, EMBASE, and MEDLINE databases. STUDY SELECTION: We included all randomized controlled trials and comparative observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 16 publications
3
24
2
Order By: Relevance
“…Using vasopressin is not entirely without bene t. The most signi cant nding was that vasopressin as a part of VSE did improve the rate of ROSC for IHCA patients but did not improve mild-term survival and mild-term good neurological outcome. The nding was inconsistent with the results of a previous metaanalysis (25) that suggested that VSE are associated with improved outcomes in cardiac arrest, including good neurologic outcome, survival to hospital discharge and ROSC. Three trials receiving VSE were included, and three trials used the same VSE protocol during CPR, as shown in the Table 1.…”
Section: Discussioncontrasting
confidence: 67%
“…Using vasopressin is not entirely without bene t. The most signi cant nding was that vasopressin as a part of VSE did improve the rate of ROSC for IHCA patients but did not improve mild-term survival and mild-term good neurological outcome. The nding was inconsistent with the results of a previous metaanalysis (25) that suggested that VSE are associated with improved outcomes in cardiac arrest, including good neurologic outcome, survival to hospital discharge and ROSC. Three trials receiving VSE were included, and three trials used the same VSE protocol during CPR, as shown in the Table 1.…”
Section: Discussioncontrasting
confidence: 67%
“…As noted in our limitations, the majority of randomized controlled trials (RCTs) included in our analysis contained a high risk of bias in at least one domain, limiting the inherent validity of our findings. These results are presented in our article (2) in Figure 2. However, this should not preclude a quantitative analysis of results as it is common for meta-analyses to include studies that may differ with respect to their risk of bias (such as randomization, allocation concealment, etc.…”
supporting
confidence: 69%
“…A recent meta-analysis that pooled the results of these studies further confirmed significant associations between the use of these therapeutic adjuncts and return of spontaneous circulation, survival to hospital discharge, and survival with good neurological function. 7 In this issue of JAMA, Andersen and colleagues 8 report findings of the VAM-IHCA randomized clinical trial, a multicenter study to evaluate the efficacy of vasopressin and methylprednisolone administered in combination with standard advanced life support, including use of epinephrine, during resuscitation among patients who experienced…”
mentioning
confidence: 99%